2005
DOI: 10.1111/j.1600-079x.2005.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective CCK‐A but not CCK‐B receptor antagonists inhibit HT‐29 cell proliferation: synergism with pharmacological levels of melatonin

Abstract: Some data suggest that cholecystokinin (CCK) receptor agonists stimulate the growth of colon cancer. Melatonin, an endogenous indoleamine with strong antioxidant properties, displays antiproliferative and proapoptotic properties both in vivo or in vitro in several types of tumors. We used HT-29 human colon cancer cells, expressing CCK receptors, to test the antiproliferative effects of several antagonists of CCK-A and/or CCK-B and their possible synergism with melatonin. HT-29 cells were cultured in RPMI 1640 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Along the same lines, Gonzalez‐Puga et al. [175] reported that the indoleamine significantly inhibited cell proliferation and increased cancer cell death. Interestingly enough, melatonin acted synergistically with several CCK‐A antagonists, mainly devazepide, to further reduce HT‐29 cell growth.…”
Section: Responses Associated With Melatonin In Ibd and Colon Cancermentioning
confidence: 87%
“…Along the same lines, Gonzalez‐Puga et al. [175] reported that the indoleamine significantly inhibited cell proliferation and increased cancer cell death. Interestingly enough, melatonin acted synergistically with several CCK‐A antagonists, mainly devazepide, to further reduce HT‐29 cell growth.…”
Section: Responses Associated With Melatonin In Ibd and Colon Cancermentioning
confidence: 87%
“…For example, in human HT‐29 CRC cells 1 mM melatonin for 24 hours increased flavone‐triggered apoptosis by incorporating oxidizable substrates into mitochondria. Also, melatonin enhanced chromatin condensation and DNA fragmentation, as well as 0.5‐2 mM inhibited uncontrolled cell proliferation and stimulated apoptosis in a dose‐dependent manner . In human SW480 and LoVo cells, 1 mM melatonin for 48 hours potentiated the apoptotic and antimetastatic effects, in combination with ursolic acid.…”
Section: Synergistic Actions Of Melatonin As Adjuvant Treatment In Crcmentioning
confidence: 93%
“…The immunomodulatory effects of melatonin and its antineoplastic properties are currently under intensive investigation [89,90] . Experimental studies, carried out on animal models have demonstrated that pinealectomy enhances tumor growth and metastatic spread [91] .…”
Section: Melatonin As Single Antitumor Treatmentmentioning
confidence: 99%